Strategies for Alleviating Language Anxiety in Students’ Academic Speaking Performance - Vina Asterina; Muhammad Tahir; Fitriyani Bakri (International Journal of Language, Education, and Literature, 2025)
Language anxiety represents a significant barrier for English as Foreign Language (EFL) learners, particularly in academic speaking tasks where performance pressure is elevated. This study aimed to identify the strategies second-semester English Literature students employed at Universitas Balikpapan to alleviate anxiety during academic speaking activities. Utilizing a descriptive qualitative research design, data were collected through semi-structured, face-to-face interviews with 20 purposively selected students who reported experiencing speaking anxiety. The interviews consisted of five key questions designed to elicit detailed descriptions of students’ experiences with language anxiety and their coping mechanisms. Thematic analysis revealed four main strategies consistently employed by students to manage language anxiety during academic speaking: preparation, relaxation, conviction, and resignation. Preparation emerged as a frequently reported strategy, wherein students meticulously practised their presentations, organized notes, and rehearsed vocabulary to build confidence (8 students). Relaxation techniques, including deep breathing, positive self-talk, and listening to music before presentations, were widely used to calm nerves (10 students). Conviction involved fostering a mindset of self-belief and positive affirmation, with students recognizing that mistakes are an integral part of learning (3 students). Lastly, some students adopted a strategy of resignation, accepting their anxiety but proceeding with the task regardless, often viewing it as a necessary challenge (2 students). These strategies varied according to individual coping styles and levels of self-efficacy. The findings underscore the importance of managing language anxiety to enhance academic speaking performance. The study recommends that educators cultivate supportive classroom environments and incorporate explicit anxiety-reduction techniques into speaking curricula. This research contributes novel insights by focusing specifically on anxiety management within academic speaking tasks, offering practical guidance for improving pedagogical approaches in EFL education. Future research could explore the long-term effectiveness of these strategies and the impact of instructor-led interventions on students’ anxiety management skills.